Fabrication-aware shape parametrisation for the structural optimisation of shell structures. (1st December 2018) - Mesnil, Romain; Douthe, Cyril; Richter, Christiane; Baverel, Olivier
Highlights: Shape optimization of shells usually yields structures that are difficult to build. A shape parametrisation method resulting in PQ-meshes is implemented as a CAD tool. A comparative study with NURBS modelling illustrates the potential of the method. Structurally optimal design resulting from the proposed framework are constructible. Abstract: The difficulty to construct mechanically optimal shells may limit the use of structural optimisation in practice. The objective of this paper is to propose a new parametric representation of doubly curved shapes suited for structural optimisation of architectural shells that inherently considers fabrication constraints. We focus on a common construction constraint: the covering of building envelopes with planar facets. This paper proposes to implement the so-called marionette technique as a Computer-Aided-Design tool that guarantees covering of free-form shapes with planar quadrilateral facets. General considerations on the size and nature of the optimisation space created with this method are made. It is demonstrated through different case-studies that the quality of the parametrisation for shape optimisation of shell structures is similar to the one offered by Bézier surfaces, an ubiquitous modelling technique. The proposed method conciliates thus fabrication and structural performance.